Capital and Trade As Engines of Growth in France : An Application of Johansen's Cointegration Methodology - Coe, David (IMF Working Papers; Working Paper ;, 1993)
An aggregate production function is estimated with recent cointegrating techniques that are particularly appropriate for estimating long-run relationships. The empirical results suggest that the growth of output in France has been spurred by increased trade integration within the European Community and by the accumulation not only of business sector capital-the only measure of capital included in most empirical studies-but also by the accumulation of government infrastructure capital, residential capital, and R and D capital. Calculations of potential output indicate that trade and capital-broadly defined-account for all of the growth in the French economy during the last two decades.